Exploring the intentions of pharmacy students towards pharmacy ownership by using theory of planned behaviour. (December 2016) - Khan, Muhammad; Ahmad, Akram; Fayyaz, Muhammad; Ashraf, Nida; Bhagavathula, Akshaya
Abstract Objective The objective of this study was to assess the association of the constructs of theory of planned behaviour (behavioural beliefs, normative beliefs, control beliefs) and demographic variables with the intentions of pharmacy students to become pharmacy owner. Methods A cross sectional study was conducted between October and November, 2014, using a pretested, self-administered questionnaire delivered to a sample of 350 pharmacy students at a private university of Pakistan. Behavioural beliefs, normative beliefs and control beliefs were assessed on four point Likert scale of agreement. The scores were summed and dichotomized based on an arbitrary 50 % cut-off score to assess positive and negative beliefs. Binary logistic regression was used to analyse the data. Results A total of 313 participants (89.4 %) responded to the questionnaire. Participants' behavioural beliefs, normative beliefs and control beliefs were negative towards pharmacy ownership with the mean scores of 13.90  ± 0.41 (score range: 6–24), 9.66 ± 0.49 (score range: 4–16) and 16.88 ± 0.40 (score range: 7–28) respectively. Professional year and family business were significantly associated with intentions of pharmacy students to own a pharmacy (p < 0.05). Conclusion Behavioural beliefs, normative beliefs and control beliefs were negative towards pharmacy ownership. Implementation of entrepreneurship course in pharmacy school may transform the beliefs of pharmacy students towards pharmacy ownership.